Music performance anxiety: Conceptual introduction and Peruvian cases - Chang-Arana, Álvaro Mario (2020)
Music performance anxiety (MPA) is a complex phenomenon with potentially serious consequences for musicians. In this article I summarize recent literature on this dynamic field of study. Specifically, I will unpack the following topics: definition, consequences, prevalence and treatments, and limitations. Having explained these topics, I reserve the last section to summarize the study of MPA in Peru. This article aims to stimulate an open and scientific discussion of MPA which can inform pedagogical and professional practices for the benefit of the musicians’ well-being. Additionally, the article contributes to the available literature in Spanish, given that the majority of studies on MPA are reported in English-language forums.